LAPORAN AKUNTABILITAS KINERJA BADAN LINGKUNGAN HIDUP KABUPATEN PASURUAN: PERSPEKTIF VALUE FOR MONEY - Mandasari, Erly Putri; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the presentation of performance accountability statement on the Environmental Agency in Pasuruan district based on the guideline regulations of State Minister for the Empowerment of State Apparaturs Bureaucratic Reform Nomor 29 of 2010 and to evaluate the performance of Environmental Agency which is reflected on the performance statement by using the value for money approach. This research has been prepared by using qualitative descriptive method. The result of the discussion and the analysis shows that the performance accountability statement of Environment Agency in Pasuruan district in 2014 has been presented in accordance with the guideline regulations of State Minister for the Empowerment of State Apparaturs Bureaucratic reform Nomor 29 of 2010. The performance of the institution has been running well, but there are some results of implementation programs which have not been achieved optimally. The Environment Agency in Pasuruan district in determining the economic performance is done by considering the input to the market prices. The efficiency of the performance can be seen from the realization of the output which has been generated to the input which is budget. The performance effectiveness can be known from the output and outcome which has successfully run well the institution goals, so the relevance of output and outcome indicators is required to be developed by considering its relevance with the goals and activities of the program. Although the Environment Agencys performance Pasuruan are presented in the performance already demonstrated by the plan nevertheless necessary to develop indicators of value for money that was relevant to the purpose of the implementation of programs and activities.Keywords: Performance and Accountability Report of Government Agencies (LAKIP), Value for Money, Economic, Efficiency, Effectiveness.